Feline platynosomiasis in Klang Valley, Malaysia: diagnosis, pathology and management - N., Nur Amalina; Watanabe, M.; M., Mazlina; Che Amat, A.; A. A., Nor Azlina (Malaysian Society of Parasitology and Tropical medicine, 2022)
Platynosomum fastosum (synonym Platynosomum concinnum, Platynosomum illiciens) is a hepatic fluke causing platynosomiasis or ‘lizard poisoning’ in cats. This disease is generally being underestimated by veterinary practitioners due to lack of awareness and difficulty in diagnosis although the severe cases of platynosomiasis could be fatal. This study was designed to detect the presence of cat liver fluke through faecal examination among cats kept in shelters, pet cats and stray cats around Klang Valley, Malaysia. The detection of liver flukes among stray cats was based on post-mortem examination. A total of 201 faecal samples were collected from eight shelters (n = 119) and five veterinary clinics (n = 82) in Klang Valley were subjected to simple floatation and formalin-ether sedimentation techniques for ova detection. P. fastosum ova were identified in three faecal samples obtained from shelters (2.52%) and three samples collected from veterinary clinics (3.66%) by faecal examination. A total of 51 stray cats were procured from Pest and Animal Control Unit of the respective municipality. The cats were euthanised and necropsied to collect liver samples and bile duct. The liver was then dissected for isolation and identification of the fluke and bile duct fluid were aspirated for detection of fluke ova. Twelve cats (23.5%) were positive for P. fastosum and ova were found in their bile. Macroscopically, affected cats showed mottled liver (33.3%), distended gall bladder with thick tenacious bile (66.7%) that microscopically exhibited hepatic steatosis (25.0%) and hepatitis (33.3%). The severity of parasite load was almost equally distributed between the positive cats with low (n = 5, 55.6%; > 125 adult fluke) and high parasite burden (n = 4, 44.4%; < 125 adult fluke) cats, respectively. This study revealed the detection of P. fastosum among pet, shelters and stray cats in Klang Valley, Malaysia.